Analysis of the Similarity of Batak Language in Samosir Regency (Study Case: Nainggolan, Harian, and Otlan Runggu Sub-District) - Sumarsih Sumarsih (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Haryadi (2015) stated that dialect comes from the Greek word dialectos which matches the dialect. The research was aimed to analyze the similarity of Batak language in Nainggolan, Harian, and Otlan Runggu Sub- District  Samosir Regency, North Sumatera. The research conducted descriptive qualitative research. The research was conducted by using interview and recording as the technique of collecting data.The data were obtained from the society of Nainggolan, Harian, and Otlan Runggu Sub- District  Samosir Regency, North Sumatera. The result  of the research showed that Nainggolan, Harian, and Otlan Runggu have the similarity in Batak language use. There is no the difference of them even though those regions are in different sub-districts.